Designing a Fuzzy Inference System for Predicting the Implementation Success of ERP Solution - mohammad ali Shafia; amir Manian; iman Raeesi Vanani (Journal of Information Technology Management)
Implementation of Enterprise Resource Planning has had a chaotic history in which many projects ended successfully and many failed or ended without approaching the predetermined objectives. This research, in terms of purpose, is considered fundamental since it designs a new system for solving a fundamental problem and it is also an applied research because the research result is deployed in the organization for determining the implementation success ratio. The research utilizes the content analysis for identifying the factors and indicators and uses a survey research for gathering data from selected organizations. In this study, for overcoming the problems of implementation project, a fuzzy system has been designed, trained and validated using the Adaptive Neuro-Fuzzy Inference System so as to predict the implementation success ratio before the initiation of the project. The research output is an intelligent fuzzy inference system.